Membangun Komunikasi Ayah dan Anak Melalui Aktivitas di Rumah - Nur Inten, Dinar (UPT Publikasi Ilmiah UNISBA, 2024)
Fathers have an important position in supporting children's growth, development and education. But sometimes the role of fathers is ignored by some people, even though through the father figure the child will find the basics and figures and role models for his life. The purpose of this study is to find out how fathers build communication with children to foster harmony and close relationships between fathers and children. The method used is through literature study, namely the author examines and collects various sources related to father-child communication and then analyzes and describes them. The results of the study state that communication between fathers and children can be built through daily activities that fathers do while at home. And these activities can not only strengthen the relationship between father and child but can also help optimize child development.